Evaluation of heterocyclic hydrocarbon compounds, mainly ccarbazole compounds by Thalassospira xiamenensis, Chromohalobacter marismortui, Pseudomonas stutzeri and Thalassospira profundimaris from coast of Sarawak, Malaysia - Jane, Sebestian Taka (unimas, 2016)
A study was done to determine the presence of degradation activity of heterocyclic hydrocarbon compounds in marine bacteria isolated from seawater of Sarawak coastline. Four isolates of marine bacteria that capable of utilizing three heterocyclic hydrocarbon compounds, which were biphenyl, dibenzothiophene and carbazole as the sole source of carbon and energy for bacterial growth were isolated from three different sites in coast of Sarawak which were Muara Tebas, Sematan, Miri area and designated as MT, SEM, M, respectively. One isolate from MT, designated as MT02 showed positive utilization of dibenzothiophene. Two isolates from SEM, designated as SEM01 and SEM02, showed positive utilization of biphenyl and dibenzothiophene, respectively, and one isolate from M, designated as M02 showed positive utilization of carbazole. All four isolates were characterized biochemically and genetically by 16S ribosomal DNA sequence where MT02, SEM01, SEM02 and M02 were identified as Thalassospira xiamenensis, hromohalobacter marismortui, Pseudomonas stutzeri and Thalassospira profundimaris, respectedly.